Stunting and development of behavior - Verawati Simamora; Sabar Santoso; Nanik Setiyawati (International Journal of Public Health Science (IJPHS), 2019)
The current study aimed to examine the relationship between the incidence of Stunting, characteristics of mother with the development of toddlers 24-59 months in the work area of Sentolo I Public Health Center, KulonProgo Regency. The study design used was a retrospective cohort (historical cohort). The research was conducted in May 2019. The population of this study was all under-fives under the Sentolo Health Center I work area. There were 130 respondents consisting of 65 exposed groups and 65 unexposed groups participated in this study. The analysis used in this study used Chi-square.Developments wasdetected using Denver II. The results of the bivariate analysis showed that there was a relationship betweenStunting and the development of toddlers 24-59 months (p=0.003). There was no relationship between sex and number of siblings with the development of children under five (p=0.808). There is a significant relationship between the level of knowledge of mothers and toddler development (p=0.859). There is a relationship between the level of education of mothers with development (p=0.003). There is a relationship between family income and the development of (p=0.001), but there is no relationship between the work of mothers and children under five years (p=0.001).There is a relationship between Stunting and developing toddlers 24-59 months in the working area of Sentolo I Public Health Center, KulonProgo Regency.